Investigation on the conA binding properties of klebsiella pneumoniae - Anuar, A.S.S.; Tay, Sun Tee (Malaysian Society of Parasitology and Tropical Medicine, 2014)
Klebsiella pneumoniae is a healthcare-associated bacterial pathogen which causes severe diseases in immunocompromised individuals. Concanavalin A (conA), a lectin which recognizes proteins with mannose or glucose residues, has been reported to agglutinate K. pneumoniae and hence, is postulated to have therapeutical potential for K. pneumoniae-induced liver infection. This study investigated the conA binding properties of a large collection of clinical isolates of K. pneumoniae. ConA agglutination reaction was demonstrated by 94 (51.4%) of 183 K. pneumoniae isolates using a microtiter plate assay. The conA agglutination reactions were inhibited in the presence of 2.5 mg/ml D-mannose and 2.5 mg/ml glucose, and following pretreatment of the bacterial suspension with protease and heating at 80 degrees C. Majority of the positive isolates originated from respiratory specimens. Isolation of conA-binding proteins from K. pneumoniae ATCC 700603 strain was performed using conA affinity column and the conA binding property of the eluted proteins was confirmed by western blotting analysis using conA-HRP conjugates. Proteins with molecular weights ranging from 35 to 60 kDa were eluted from the conA affinity column, of which four were identified as outer membrane protein precursor A (37 kDa), outer membrane protein precursor C (40 kDa), enolase (45 kDa) and chaperonin (60 kDa) using mass spectrometry analysis. Several conA binding proteins (including 45 and 60 kDa) were found to be immunogenic when reacted with rabbit anti-Klebsiella antibody. The function and interplay of the conA binding proteins in bacterium-host cell relationship merits further investigation.